A data analysis framework for in vivo monitoring in carbon-ion radiotherapy (CIRT): towards 3D reconstruction of interfractional anatomical changes - Schlegel, Patrice; Kirchgässner, Rebekka; Ochoa-Parra, Pamela; Kelleter, Laurent; Gertz, Michael; Mikut, Ralf; Jäkel, Oliver; Martišíková, Mária (Physics in medicine and biology, 2025)
Objectives. Carbon-ion radiotherapy is a cancer treatment modality with exceptional precision and effectiveness compared to conventional x-ray therapy. Our goal is to support maintaining its precise dose administration throughout a multi-fractional radiation treatment by detecting possible anatomical changes decremental to conformal dose deposition without the need for additional imaging. To that end our work group has developed a custom detection system using TimePix3 trackers during treatment to detect the naturally occurring secondary charged particles, which carry information about the irradiated region. This enables treatment-day accurate in-vivo monitoring of patient anatomy without requiring additional imaging. Our goal is to provide a robust and extensible methodological framework that allows us to extract relevant information supporting clinical decision making. Approach. Comparing the measurements of different states of the same patient, we aim to determine if an anatomical change is present and at what location it occurred. Departing from solely utilizing statistical differences in local particle counts, the presented method exploits the spectral domain of the measurement differences. We perform a localized spectral analysis and exploit joint localized frequency band variations to robustly identify the location of changes between two measurement states. Main Results. We show the validity of our approach, reporting the performance results of applying our method to measurements acquired during irradiation experiments using polymethyl methacrylate head phantoms carried out at the Heidelberg Ion Beam Therapy Center. Furthermore, we demonstrate the flexibility of our analysis framework by showing the impact of applying filters or using alternative sub-modules in its multi-stage processing pipeline. Significance. We provide a data-analytical framework as well as basic analytical methods required to extract evidence for the presence of anatomical changes from secondary charged particle measurements for subsequent clinical assessment. These represent essential building blocks required to perform full 3D reconstruction of anatomical changes based solely on secondary particles.